13 Heart failure and rheumatic heart disease in india. (9th April 2018) - Karthikeyan, Ganesan
Abstract : Though rheumatic heart disease (RHD) is on the decline, it remains an important cause of heart failure (HF) in many developing countries including India. It is estimated that about 10%–15% of all HF in India is attributable to RHD. Indirect estimates from the recent Global Burden of Disease (GBD) Study indicate that the absolute number of patients with moderate to severe HF due to RHD is likely to be about 3 50 000 in India. Heart failure in RHD is due mainly to severe left-sided valve lesions or due to reactive pulmonary artery hypertension as a result of chronic and severe elevation of pulmonary venous pressures. Other causes of HF include severe primary tricuspid stenosis or regurgitation, and ventricular dysfunction due to involvement by the rheumatic process. Management of HF in RHD is mainly surgical or interventional. In selected patients with dominant mitral stenosis (MS), timely percutaneous mitral commissurotomy provides durable relief. Balloon aortic and tricuspid valvotomy are useful in some patients with aortic and tricuspid stenosis (AS, TS). Transcatheter aortic valve replacement (TAVR) is not useful due to the rarity of isolated AS and young age of patients. Valve replacement performed for regurgitant lesions and calcific valves. Mitral valve repair, though recommended, is not possible in most patients with rheumatic mitral regurgitation. Due to late presentation, some patients with regurgitant lesions develop severe ventricular dysfunction, which may not reverse with valve replacement. These patients should receive long-term guideline-directed medical therapy.